In situ determination of V(V) by diffusive gradients in thin films and inductively coupled plasma mass spectrometry techniques using amberlite IRA-410 resin as a binding layer - Luko, Karen Silva [UNESP]; Menegário, Amauri Antonio [UNESP]; Suárez, Carlos Alfredo [UNESP]; Tafurt-Cardona, Makenly [UNESP]; Pedrobom, Jorge Henrique [UNESP]; Rolisola, Ana Marta Cavinato Marchini [UNESP]; Sulato, Everton Tiago [UNESP]; Kiang, Chang Hung [UNESP] (Elsevier, 2017)
Amberlite IRA-410 anionic exchange resin was evaluated as the binding layer for sampling V(V) by using Diffusive Gradients in Thin Films (DGT). V(V) was determined by inductively coupled plasma mass spectrometry (ICP-MS). Mass vs. time DGT deployments (ionic strength = 0.03 mol L−1 NaNO3, pH = 5.6 and T = 23.5 ± 0.5 °C) was characterized by excellent linear relationship (R2 = 0.9993) and a significant retention of V(V) by the binding layer. An exchange capacity of at least 40 μg V g−1 resin was achieved for the proposed binding layer. The diffusion coefficient obtained (7.13 ± 0.6 10−6 cm2 s−1) agrees with the literature. The accumulation rate of V(V) was not significantly affected by ionic strength of solutions up to 0.03 mol L−1 and for the entire studied pH range (from 3 to 9). Furthermore, when comparing the concentrations obtained using IRA-410-DGT and those obtained by direct measurement of the solution concentrations, the proposed approach provided a reduction of the 35Cl16O interference on V(V) determination by ICP-MS. Determination of V in normal mode (without collision cell) in solutions containing analyte:Cl− concentration ratio up to 1:500,000 was not affected by interference of 35Cl16O+ polyatomic ion even when normal mode ICP-MS was used. Potential interfering ions on sampling V(V) by DGT (PO4 3− and SO4 2−) showed no significant effects on the accumulation rate of V(V). Laboratory tests performed using synthetic samples, natural freshwater and acid drainage water showed an excellent performance (recoveries from 93% to 110%). For in situ deployment, measurements of V(V) by the proposed approach was not significantly different (95.5%) from the value of dissolved V concentration.
Keywords: 35Cl16O; Agarose; DGT; ICP-MS; Vanadium